The Potential Bioactive Compound of Rhizophora Apiculata Mangrove Fruit Extract in Inhibiting the Growth of Salmonella typhi Bacteria - Herna Febrianty Sianipar; Mardame Pangihutan Sinaga; Welmar Olfan Basten Barat (Postgraduate, University of Mataram, 2025)
Infections caused by Salmonella typhi remain a serious global health problem, particularly due to the increasing bacterial resistance to conventional antibiotics. Therefore, the search for effective natural antibacterial sources is urgently needed. Rhizophora apiculata, a mangrove plant known to contain various bioactive compounds, has the potential to be an alternative antibacterial source. This study aims to identify the phytochemical content in R. apiculata fruit extract and evaluate its antibacterial activity against S. typhi using the disc diffusion method and bacterial cell morphology analysis via SEM. The phytochemical screening results revealed that the extract contains phenolics, tannins, alkaloids, and flavonoids. However, saponins and steroids were not detected. The antibacterial activity test showed that the extract at a concentration of 250 mg/mL significantly (p < 0.05) inhibited the growth of S. typhi, with the largest inhibition zone (11.6 mm). SEM observations supported this finding by showing a decrease in the number of bacterial cells at extract concentrations of 125 mg/mL and 250 mg/mL, where the highest concentration caused the most bacterial cell death. This study demonstrates the potential of R. apiculata fruit extract as an effective natural antibacterial source for the development of alternative treatments for S. typhi infections